IMPLEMENTATION OF SCIENCE LEARNING THROUGH EXPERIMENTAL METHODS OF MIXING COLORS IN EARLY CHILDHOOD AT TK NEGERI 4 BOKAN ISLANDS TOROPOT VILLAGE - Zahra, Afifah; Safitri, Riskal; Nasaruddin, Nasaruddin (Media Inovasi Pendidikan dan Publikasi, 2024)
This qualitative research focused on how science learning was implemented through color-mixing experiments for early childhood students. Data collection techniques included observations, interviews, and documentation, analyzed through data collection, data presentation, and conclusion drawing. The study revealed that 7 students demonstrated progress categorized as